1993
DOI: 10.2169/internalmedicine.32.197
|View full text |Cite
|
Sign up to set email alerts
|

A New Modified Classification of Bronchial Asthma Based on Clinical Symptoms.

Abstract: The clinical features of four asthma types, Ia-1 (bronchospasm with 0-49ml/day of expectoration), Ia-2 (with 50-99 ml/day), Ib (over 100 ml/day), and II (bronchiolar obstruction), as classified by the clinical symptoms, were compared in 119 patients with bronchial asthma. The age of onset characteristic symptomsof each asthma type was in the 20's in types Ia-1 and Ia-2, in the 30's in type Ib, and in the 40's in type II patients. A significant increase in the number of neutrophils in bronchoalveolar lavage (BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Our previous studies have shown that the role of histamine during triggering events of asthma attacks is different between younger and older patients with asthma (9). LTC, is also one of the major chemical mediators having strong bronchoconstricting action and participates in the onset pates in the onset attacks.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that the role of histamine during triggering events of asthma attacks is different between younger and older patients with asthma (9). LTC, is also one of the major chemical mediators having strong bronchoconstricting action and participates in the onset pates in the onset attacks.…”
Section: Introductionmentioning
confidence: 99%